Evidence of reporting biases in voxel‐based morphometry (VBM) studies of psychiatric and neurological disorders. Issue 7 (7th October 2013) - Fusar‐Poli, Paolo; Radua, Joaquim; Frascarelli, Marianna; Mechelli, Andrea; Borgwardt, Stefan; Di Fabio, Fabio; Biondi, Massimo; Ioannidis, John P.A.; David, Sean P.
Abstract Objectives To evaluate whether biases may influence the findings of whole‐brain structural imaging literature. Methods Forty‐seven whole‐brain voxel‐based meta‐analyses including voxel‐based morphometry (VBM) studies in neuropsychiatric conditions were included, for a total of 324 individual VBM studies. The total sample size, the overall number of foci, and different moderators were extracted both at the level of the individual studies and at the level of the meta‐analyses. Results Sample size ranged from 12 to 545 (median n = 47) per VBM study. The median number of reported foci per study was six. VBM studies with larger sample sizes reported only slightly more abnormalities than smaller studies (2% increase in the number of foci per 10‐patients increase in sample size). A similar pattern was seen in several analyses according to different moderator variables with some possible modulating evidence for the statistical threshold employed, publication year and number of coauthors. Whole‐brain meta‐analyses (median sample size n = 534) found fewer foci (median = 3) than single studies and overall they showed no significant increase in the number of foci with increasing sample size. Meta‐analyses with ≥10 VBM studies reported a median of three foci and showed a significant increase with increasing sample size, while there was no relationship between sample size and number of foci (median = 5) in meta‐analyses with <10 VBM studies. Conclusions The number of foci reported in small VBM studies and even in meta‐analyses with few studies may often be inflated. This picture is consistent with reporting biases affecting small studies. Hum Brain Mapp 35:3052–3065, 2014. © 2013 Wiley Periodicals, Inc.